1999
DOI: 10.1021/jf981028l
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Roasting on Pyrazine Contents and Oxidative Stability of Red Pepper Seed Oil Prior to Its Extraction

Abstract: Red pepper seeds were roasted with constant stirring for 6, 9, 10, and 12 min at 210 degrees C, and oils were extracted from the roasted red pepper seeds using an expeller. The iodine values and fatty acid compositions of red pepper seed oils did not change with roasting time. The fatty acid composition of the oil obtained from the red pepper seeds roasted for 6 min was 0.24% myristic acid, 13. 42% palmitic acid, 0.33% palmitoleic acid, 2.07% stearic acid, 10. 18% oleic acid, 73.89% linoleic acid, and 0.37% li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
2
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 16 publications
8
35
2
2
Order By: Relevance
“…These decreases may be attributable to reductions in the number of unsaturation sites as a result of oxidation, polymerization, or breakage of the long-chain FA. However, Jung et al (32) reported that the iodine values of red pepper seed oils did not change with roasting time. In sunflower seed and peanut oils, Yoshida et al (2,33) found that roasting caused a significant decrease (P < 0.05) in molecular species containing more than four double bonds.…”
Section: Resultsmentioning
confidence: 98%
“…These decreases may be attributable to reductions in the number of unsaturation sites as a result of oxidation, polymerization, or breakage of the long-chain FA. However, Jung et al (32) reported that the iodine values of red pepper seed oils did not change with roasting time. In sunflower seed and peanut oils, Yoshida et al (2,33) found that roasting caused a significant decrease (P < 0.05) in molecular species containing more than four double bonds.…”
Section: Resultsmentioning
confidence: 98%
“…However, the differences were not statistically significant (p > 0.05). Others have reported that roasting caused no significant variation in fatty acid composition of extracted oils (Jung, Bock, Baik, Lee, & Lee, 1999;Kim et al, 2002).…”
Section: Fatty Acid Compositionmentioning
confidence: 95%
“…Oils, extracted from coated and unhulled seeds after microwaving, are oxidized more quickly than those from other treatments (Abou-Gharbia et al, 1997). Some studies have shown that the chemical composition of oil is independent of the roasting temperature used for its preparation (Kim et al, 2002;Jung et al, 1999).…”
Section: Introductionmentioning
confidence: 99%